A pensão previdenciária pública, as emendas constitucionais e a segurança jurídica - Munari, Márcia Maria Corrêa (2008)
The work establishes an analysis on behalf of the Constitution Law about the public welfare pension benefit. First, it develops the historical evaluation of the Constitutionalism and the death pension in the Brazilians Constitutions. Then, it gives emphasis to the Constitution of 1988 and the right of the integrality of the death pension left by the civil servant, regarding jurisprudence. It deals, afterwards, with the public welfare reforms that turned into the Amendments 20/98 and 41/03, with approach towards the tribute problem and the situations inflicted by the summit wage. At the end, it outlines the relation lead by the principle of Juridical Security and the public death pension